Purchase Now or Later? Attracting Strategic Consumers With an Extended Warranty: A Study of New and Reman Products - P. Jalapathy; M. Mubashir Unnissa (IEEE Access)
Extended warranties have emerged as a strategic imperative for Original Equipment Manufacturers, playing a pivotal role in fostering consumer trust and influencing their preference between remanufactured and new products. It is customary for vendors to integrate extended warranties and lower product prices towards the end of a selling season, thereby prompting consumers to manage their purchasing timing tactically. In light of consumers’ strategic behavior, Original Equipment Manufacturers are compelled to meticulously determine both product pricing and warranty offerings to uphold profitability. The paper delves into the retailing strategies and optimal pricing decisions with extended warranty of Original Equipment Manufacturers within a Closed−Loop Supply Chain. This exploration takes into consideration two distinct consumer types: myopic and strategic. Additionally, the analysis accounts for a limited volume of product returns and the level of consumer acceptance regarding remanufactured products. The study seeks to investigate the impact of extended warranty and the discounting rate of consumers’ perceived value regarding deferred purchases. The findings suggest that the Original Equipment Manufacturers retail strategy and prices is significantly influenced by the unit manufacturing/production and (re)manufacturing costs, as well as the composition of the consumer base when extended warranty is offered. The results of the numerical experiments yield additional insights to implement straightforward countermeasure strategies with extended warranty.